Coal mining-induced composite damage to geological bodies and geological guarantee against damage reduction - Shuangming WANG; Qiang SUN; Xin HU; Jishi GENG; Enke HOU; Shengquan WANG; Shutao ZHOU; Qingmin SHI; Shihao YUAN; Kai CHEN; Shijie SONG (Meitian dizhi yu kantan)
Objective and Background Coals have long served as a predominant energy source in China. With an increase in mining scale and intensity in recent years, the correlations between rocks, soils, hydrosphere, and ecological environment in coal mining areas have been strengthened. Given this, there is an urgent need to, from the perspective of Earth system science, understand the coupling relationships and chain characteristics among factors including the movement and deformations of surrounding rocks, rock bursts, coal and gas outbursts, water inrushes, ground subsidence, water and soil erosion, and damage to ecological environments, aiming to achieve safe, green coal mining. Methods and Results Based on geological structure control and mining-induced responses of rock mass structure, this study proposes scientific research on composite damage to geological bodies, including content, key issues, and geological guarantee philosophies for damage reduction. Specifically, it is necessary to research the combination relationships of coals, rock water, soils, and ecosphere in coal mining areas, as well as their dynamic response characteristics. This will help analyze the basic geological conditions for the formation of composite damage, ascertain the dynamic evolution characteristics of the geological conditions of various spheres before, during, and after mining under the background of coal development, and establish a dynamic coupling and evolution model of coals, rocks, water, soils, and ecosystems. There is a need to establish a collaborative driving model of the composite damage. This will assist in accurately identifying and quantifying key state parameters of various elements, identifying damage types and their primary controlling factors, and revealing the multi-field coupling response laws to coal mining and the evolution process of composite damage. It is supposed to, based on the correlations between multi-sphere damage under coal mining, pay much attention to the dynamic evolution process of composite damage and corresponding changes in key state parameters and, accordingly, establish a collaborative prediction, monitoring, and prevention system against composite damage in coal mining areas. Furthermore, it is necessary to build five systems and one platform, i.e., a precise exploration system, an intelligent perception system, a rapid interpretation system, a risk assessment system, an engineering loss reduction system, and a comprehensive analysis platform for mining-induced composite damage. These systems and the platform are supposed to scientifically analyze natural factors such as coal burial conditions, rock mass structure conditions, hydrogeological conditions, and ecological conditions, as well as geological information like multi-sphere response laws of rocks, waters, soils, and ecosystems. The purpose is to achieve transparent geological structure conditions, effective evaluation models and methods, optimized coal development models, advanced prediction of risk dynamics, and scientific strategies for geological security. Additionally, research on the geological guarantee against composite damage to coal mine surrounding rocks can provide scientific guidance for damage reduction during coal mining and contribute to green, safe coal mining and ecological protection.